Analysis of the Effect of Indonesia-Japan Economic Partnership Agreement (IJEPA) on the Trade in Service Sector in Indonesia - Syahputri, Evanti Andriani; Gupta, I Made Krisna Yudhana Wisnu (Jurnal Manajemen Industri dan Logistik, 2024)
The Economic Partnership Agreement (EPA) is a trade agreement that aims to facilitate market access and considers aspects of economic cooperation and development initiatives between the two countries. The trade agreement between Indonesia and Japan is Indonesia's first bilateral trade agreement covering trade in goods, services, and investment, and entered into force in 2008. The development of the service sector is an important factor in supporting economic growth. This study uses panel data regression with the estimation method used by the gravity model with Difference in Difference (DiD) to see the impact of the IJEPA. The study results show that the interest variable is not significant to the dependent variable, illustrating that the existence of the IJEPA agreement is statistically unable to explain the relationship that occurs with the value of exports and imports of the Indonesian service sector. Implementing IJEPA in Indonesia still does not have an impact and has not provided benefits, especially for service trade.